Effects of ergonomics intervention on work accidents in the construction sector and their effect on productivity - Ia Asih; Indra Setiawan; Hernadewita Hernadewita; Hendra Hendra (Universitas Serang Raya, 2022)
Construction services are one of the most important and strategic sectors supporting the achievement of development in Indonesia. Through this sector, Indonesia can experience stable economic growth. In 2020, accidents in the construction sector were the highest cases compared to other sectors, with a death rate of more than 60,000 cases annually. The role of Occupational Health and Safety (OHS) Management and the application of its requirements when working at heights is crucial to protect against the dangers of work accidents due to high risk. This study aims to determine the relationship between the factors that affect work accidents in the construction sector and their effect on Productivity moderated by ergonomics. This research was conducted by analyzing surveys from work-at-height workers in the construction sector, with 107 respondents from projects in Jakarta. The data analysis method used is Structural Equation Modeling (SEM) based on non-covariance, namely Partial Least Square (PLS). Data analysis using Smart PLS 3.0 software. The results show that Ergonomics has no direct effect on Productivity, with p-value 0.313. Work Accidents do not directly affect Productivity with p-value 0.333. OHS Management does not directly affect Work Accidents with p-value 0.013. OHS Management has a direct effect on Productivity with p-value 0.000. Application of OHS Requirements has a direct effect on Work Accidents with p-value 0.527. Application of OHS Requirements has a direct effect on Productivity with p-value 0.001 and Application of OHS Requirements through Ergonomics has no direct effect on Productivity with p-value 0.000.